Distributed Electric Field Induces Orientations of Nanosheets to Prepare Hydrogels with Elaborate Ordered Structures and Programmed Deformations. Issue 47 (20th October 2020) - Zhu, Qing Li; Dai, Chen Fei; Wagner, Daniel; Daab, Matthias; Hong, Wei; Breu, Josef; Zheng, Qiang; Wu, Zi Liang
Abstract: Living organisms use musculatures with spatially distributed anisotropic structures to actuate deformations and locomotion with fascinating functions. Replicating such structural features in artificial materials is of great significance yet remains a big challenge. Here, a facile strategy is reported to fabricate hydrogels with elaborate ordered structures of nanosheets (NSs) oriented under a distributed electric field. Multiple electrodes are distributed with various arrangements in the precursor solution containing NSs and gold nanoparticles. A complex electric field induces sophisticated orientations of the NSs that are permanently inscribed by subsequent photo‐polymerization. The resultant anisotropic nanocomposite poly( N ‐isopropylacrylamide) hydrogels exhibit rapid deformation upon heating or photoirradiation, owing to the fast switching of permittivity of the media and electric repulsion between the NSs. The complex alignments of NSs and anisotropic shape change of discrete regions result in programmed deformation of the hydrogels into various configurations. Furthermore, locomotion is realized by a spatiotemporal light stimulation that locally triggers time‐variant shape change of the composite hydrogel with complex anisotropic structures. Such a strategy on the basis of the distributed electric‐field‐generated ordered structures should be applicable to gels, elastomers, and thermosets loaded with other anisotropic particles or liquid crystals, for the design of biomimetic/bioinspired materials with specific functionalities. Abstract : Hydrogels with sophisticated ordered structures at the macroscopic scale are facilely developed by using a distributed electric field to align the nanosheets (NSs), followed by polymerization and gelation. The anisotropic structures of NSs are programmable by tuning the electric field generated by the distributed multiple electrodes with specific arrangements. Upon heating or light irradiation, the composite hydrogels exhibit programmable deformations and locomotion.